Informational support and information-seeking during transition to parenthood: Baby Buddy Forward's focus groups with pregnant women and new mothers in Cyprus - Koliandri, Ioanna; Hadjigeorgiou, Eleni; Karanikola, Maria; Kolokotroni, Ourania; Nicolaou, Christiana; Christodoulides, Veronika; Papadopoulou, Maria; Kouta, Christiana; Middleton, Nicos (My University, 2023)
Relevant and accurate information during the transition to parenthood is vital for active participation in decision-making. The aim of the study was to gain an in-depth understanding of informational support and information-seeking practices among women in Cyprus during the transition to parenthood with a focus on the use of the internet and informed decision making.
Keywords: decision making; information seeking; informational needs; mothers; pregnant women